Generalized training effects induced by athletic preparation. A review - Issurin, V. B. (The Journal of Sports Medicine and Physical Fitness, 2009)
The present review deals with training effects produced by training pieces of different duration. Athletes` responses to training workloads can be considered hierarchically, where the most intimate level encompasses changes produced at the cellular and molecular levels, while the generalized level summarizes the most integrative training outcomes, which characterize athletes` adaptability, preparedness and readiness for forthcoming workloads. These training outcomes, called generalized training effects (GTE) are considered to be closely linked with duration and mode of training workloads. Summarizing earlier and more recent publications, GTEs are categorized as acute, immediate, cumulative, delayed and residual training effects, which encompass changes induced by 1) a single exercise; 2) a single workout or training day; 3) a series of workouts; or 4) obtained over a given time interval after a program completion ; or (5) changes retained after cessation of training beyond a give time period. Each one these GTEs has a three-fold characterization:1) variables of executed workloads; 2) athletes` responses to workloads and training-induced changes in their state; 3) changes in athletic performance as described by sport specific indicators. Although the concept of GTE is far from complete in terms of an understanding of the physiological mechanisms underlying the short-, medium-, and long-term changes caused by athletic training, a number of fundamental theories and statements contribute to its scientific background. They are Cannon`s theory of homeostasis; Salye`s theory of stress adaptation; Weigert`s law of supercompensation; and Lamarck`s classic theory of evolution regarding the "use" and "disuse" of any organ or function.